“Don’t Let Medicines Go to Waste”—A Survey-Based Cross-Sectional Study of Pharmacists’ Waste-Reducing Activities Across Gulf Cooperation Council Countries - Alhomoud, Faten (Frontiers in Pharmacology, 2020)
Objectives Medication waste has a negative environmental and economic impact. From avoiding unnecessary supply to recycling medicines that are no longer needed, pharmacists are placed in an advantageous position to minimise medication waste. Thus, the aim of this study was to detect waste-minimising activities undertaken by pharmacists to limit medication waste and to evaluate their importance for medication waste minimisation and feasibility for implementation. Methods A cross-sectional survey of 277 participants, conveniently selected from six Gulf countries. The eligibility criteria were pharmacists or pharmacy technicians, Arabic- or English-speaking individuals, aged ≥18 years, and living in the Gulf countries. An online self-administered survey was distributed during December 2019 and February 2020, via email and social networks; it included the purpose of the study with a link to the webpage that hosted the questionnaire. Data were collected through the online survey site QuestionPro.com. All analyses were performed in SPSS version 23 and Microsoft Excel. Results The majority of participants were female (175/277; 63%), hospital pharmacists (206/277; 74%), and had more than 10 years of work experience (100/277; 36%). This study indicates that most of the suggested activities (14/21) were implemented by the majority of pharmacists for minimising medication waste, except four activities in the dispensing stage and three activities in the leftover stage. Activities performed at the prescribing, dispensing and leftover stages were considered very important or important for reducing medication waste and very feasible or feasible for implementation in practice. Conclusions Many waste-minimising activities were undertaken by pharmacists in the prescribing, dispensing and leftover stages. However, although waste-minimising activities were perceived as important for reducing waste and feasible for implementation in practice, not all activities were implemented in daily practice.